Cancer-cell-secreted miR-204-5p induces leptin signalling pathway in white adipose tissue to promote cancer-associated cachexia - Yong Hu; Liu Liu; Yong Chen; Xiaohui Zhang; Haifeng Zhou; Sheng Hu; Xu Li; Meixin Li; Juanjuan Li; Siyuan Cheng; Yong Liu; Yancheng Xu; et al. (Nature Communications, 2023)
Abstract Cancer-associated cachexia is a multi-organ weight loss syndrome, especially with a wasting disorder of adipose tissue and skeletal muscle. Small extracellular vesicles (sEVs) serve as emerging messengers to connect primary tumour and metabolic organs to exert systemic regulation. However, whether and how tumour-derived sEVs regulate white adipose tissue (WAT) browning and fat loss is poorly defined. Here, we report breast cancer cell-secreted exosomal miR-204-5p induces hypoxia-inducible factor 1A (HIF1A) in WAT by targeting von Hippel-Lindau (VHL) gene. Elevated HIF1A protein induces the leptin signalling pathway and thereby enhances lipolysis in WAT. Additionally, exogenous VHL expression blocks the effect of exosomal miR-204-5p on WAT browning. Reduced plasma phosphatidyl ethanolamine level is detected in mice lack of cancer-derived miR-204-5p secretion in vivo. Collectively, our study reveals circulating miR-204-5p induces hypoxia-mediated leptin signalling pathway to promote lipolysis and WAT browning, shedding light on both preventive screenings and early intervention for cancer-associated cachexia.